Estudio De Aguas Residuales En El Bloque Administrativo Y Plantas Productivas Del Sena Agroindustrial Regional Quindío (2012)
Water is a demanded object for all living species, and contributes to society development. Thus it is necessary its study and that is why a study of wasted water was carried out in four places of SENA Agroindustrial from Quindío, Livestock, Pig production, Milk Laboratory and Administrative Block, analyzing physical-chemical and bacteriological parameters in the laboratories of Universidad del Quindío and C.R.Q.; taking in total eight compound samples, carried out in four sampling each one, through volumetrical samples; for the analysis of the results it was carried out a Krusskall-Wallis test and moreover a Pearson correlation analysis between the Physical Chemical and bacteriological parameters. Finally, the averages of organical charges were obtained. The results showed that the averages of DBOs and DQO were the highest for pig production (9.522 mg/l O2) respectively; in the Milk laboratory the results showed high averages of OD (1,88 mg/l O2), SS (3.447 mg/l), ST (19.502 mg/l) y STD (16.024 mg/l), being on contrast with the PH value ( 5,48 Units), while the Administrative Block, Pig production and Livestock had the highest values respectively regarding with CF (1,60 UFC/100 ml, 3,60 UFC/100 ml and 1,8 UFC/100 ml) and CT (5,50 UFC/100 ml, 5,60 UFC/100 ml and 2,10 UFC/100 ml). To conclude, for places which were tested contribute to the contamination of La Florida brook in its high zone and to the generation of odours which are perceived in the surrounded area, according to the Act 1594 of 1984; thus, some mitigation recommendations are suggested.